RARS: a Resource-Aware Replica Selection and co-allocation scheme for mobile grid. (2nd August 2010) - Chang, Yue-Shan; Zou, Guo-Jie; Chang, Ching-Lung
This paper presents a design for a mobile data grid architecture using agent technology, on which is based our proposed Resource-Aware Replica-Scheduling co-allocation algorithm for the mobile data grid environment. Mobile clients can access replicas of desired data from parallel, mobile grid nodes. These offer effective, efficient and reliable ways of using a variety of superior resources, such as the remaining energy, the bandwidth and the stability of connection in the nodes. The simulations presented here show that the RARS performs excellently and in the transmission time and the survival rate of the mobile nodes it exceeds all other approaches.